FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PARTISIPASI IBU KE POSYANDU DI WILAYAH KERJA PUSKESMAS BAKUNASE - Ludji Wadu, Femy; Talahatu, Anna; Boeky, Daniela (Jurnal Pangan Gizi dan Kesehatan, 2023)
This study aimed to determine the factors related to the level of maternal participation in posyandu in the working area of ​​the Bakunase Health Center. The type of research was analytical research with a cross-sectional study approach. This study's sample was all mothers with children under five aged 0-59 months, totaling 310 respondents. Used in this study was univariate and bivariate analysis with the Chi-Square test. The results showed that there is no relationship between mother’s age and the level of participation of mothers to posyandu with a value of P = 0.197 (P> 0.05), there is no relationship between mother’s work and Mother’s participation rate to posyandu with P-0.764 (P>0.05), there is no relationship between mother’s education and mother’s participation rate to Posyandu with P-value 0.679 (P>0.05), was a significant relationship between the mother’s knowledge and the mother’s level of participation in posyandu with p-value = 0.000 (p <0.05), there was a relationship There is a significant relationship between the husband’s support and maternal involvement in posyandu with a value of P = 0.003 (P < 0.05) posyandu with the participation rate of mothers to posyandu with a value of P = 0.042 (P < 0.05).